Pengaruh Literasi Keuangan, Sosialisasi Orang Tua, dan Teman Sebaya Terhadap Perilaku Menabung Mahasiswa Ekonomi dan Bisnis Universitas Negeri di Surabaya - Kristiyanti, Priskila (Jurnal Ilmiah Wahana Pendidikan, 2024)
Saving Behaviour is very influential thing in economic development in Indonesia. This study aims to analyze the influence between financial literacy, socialization of parents, and friends of student in economics and business at state university in Surabaya. This type of research is quantitative research with a total sample of 412 respondents. The object of this research is student in economics and business at state university in Surabaya. The data analysis technique used is multiple linear regression analysis and uses IBM SPSS version 25. The results of the study are that partially financial literacy, parental socialization, and peers have a positive effect on student saving behaviour. The results of the study are that there is an influence between financial literacy on saving behaviour, this is because students understand personal financial knowledge, savings and savings knowledge, insurance knowledge, and investment knowledge so that students are able to make priorities regarding financial management. There is an influence of parental socialization on saving behaviour, this is because students grow by following directions from their families, especially their parents, so that students get used to following their parents' teachings. There is peer influence on student saving behaviour, this is because in the world of lectures, students tend to spend time with friends so that the intensity of meetings and communication with peers tends to be greater.